Aerodynamics of unconventional airfoils - Ng, Bing Feng. (2009)
This project will explore lift enhancement methods for MAVs under low Reynolds number flight where CLmax are significantly lower. It will study the beneficial effects of vortices to enhance lift through both Static and Dynamic Leading Edge Vortices (LEVs). LEVs create an area of suction which generates a low pressure region to increase lift.